THE INFLUENCE OF COGNITIVE FINANCE, FINANCIAL LITERACY, FINANCIAL PLANNING, AND FINANCIAL SATISFACTION ON STOCK INVESTMENT BEHAVIORAL INTENTIONS (Case Study of Young Entrepreneurs in Lhokseumawe City) - Chiril Akhyar; Ulya Alfajri; Ristati; Jummaini (PT. Radja Intercontinental Publishing, 2024)
This research aims to determine the influence of cognitive finance, financial literacy, financial planning, and financial satisfaction on behavioral intentions to invest in shares. The research method used in this research is quantitative research. The population in this research is young entrepreneurs from Lhokseumawe City who intend to invest in shares, by taking a sample of 96 respondents using a purposive sampling technique. The data collection method in this research is by distributing questionnaires online and directly to young entrepreneurs in Lhokseumawe City. The data analysis used is multiple linear regression. The aim of this research is to find out how much young entrepreneurs in Lhokseumawe City invest in shares. This data was obtained after distributing questionnaires to young entrepreneurs whose criteria had been determined. The research results show that partially the cognitive financial variables and financial satisfaction have a significant effect on the behavioral intention to invest in shares by young entrepreneurs in Lhokseumawe City, while the variables financial literacy and financial planning do not significantly influence the behavioral intention to invest in shares. Based on the research results, the most dominant variable is cognitive finance, which greatly influences young entrepreneurs in Lhokseumawe City to invest in shares.